“Uterine Dehiscence: A Diagnostic Conundrum in Repeat Cesarean Deliveries” - Pamela Sarue; Nicholas Eynon; Reine A. Zbeidy (Clinical Case Reports)
ABSTRACT Uterine dehiscence (UD), often asymptomatic and underdiagnosed, is a significant risk in patients with prior cesarean deliveries. Serious complications include uterine rupture; increasing maternal and neonatal morbidity. Improved diagnostic protocols, particularly antenatal imaging, are essential to differentiate UD from placenta accreta spectrum, optimize resource utilization, and enhance patient outcomes.